Perbandingan Komposisi Tumbuhan Lumut Epifit Pada Hutan Alam, Kebun Kopi dan Kebun Teh di Sepanjang Gradien Ketinggian Gunung Ungaran, Jawa Tengah - Perwati, Lilih Khotim; Rahadian, Rully; Baskoro, Karyadi (Bioma : Berkala Ilmiah Biologi, 2015)
Study on the impact of differences in altitude and land use changes was conducted in natural forest, coffee and tea plantations in along altitudinal gradient of Ungaran mountain from 750 to 2040 m a.s.l. The objective of this study were to compare composition of epiphytic bryophytes species in third sites. Epiphytic bryophytes sampling were done in plots 20 x 30 cm were applied on height of tree betwen 0-2 m. A total of 103 species of epiphytics bryophytes were identified, involve 58 species of mosses (Bryophyta Division) and 45 species of liverworts (Marchantiophyta Division). The composition of bryophytes in natural forest is more diverse than in coffee and tea plantations. Lejeunaceae have the highest number of species. There are seven life forms of epiphytic bryophytes in the present study i.e. Turf, Cushion, Mats, Wefts, Dendroid, PendantÂ  and Fans. The most common is Mats and Turf form, while Pendant and Dendroid form only found in natural forest. Â  Key words: Bryophytes, epiphytes, altitude, land use changes, life form